E‐cigarette use in pregnancy: a human rights‐based approach to policy and practice. (14th September 2017) - van der Eijk, Yvette; Petersen, Anne Berit; Bialous, Stella A.
Abstract: The health risks associated with e‐cigarette use in pregnancy are mostly unknown. Guidelines by the World Health Organization and national health agencies warn women against using e‐cigarettes in pregnancy; however, in the UK, a recent multiagency guideline takes a different approach by not discouraging e‐cigarette use in pregnancy. Furthermore, e‐Voke ™, an e‐cigarette, has been approved for use in pregnancy in the UK. We analyze United Nations human rights treaties to examine how they might inform best practice recommendations for e‐cigarette use in pregnancy. These treaties oblige Parties to adopt policies that protect children's and women's right to health, appropriate pregnancy services, and health education. We argue that clinical practice guidelines related to use of e‐cigarettes in pregnancy should consider both evidence and human rights principles, and ensure that healthcare providers and patients are given clear, accurate messages about the known and potential risks associated with e‐cigarette use in pregnancy.